2022
DOI: 10.1136/emermed-2021-211751
|View full text |Cite
|
Sign up to set email alerts
|

Refining sonographic criteria for paediatric appendicitis: combined effects of age-based appendiceal size and secondary findings

Abstract: ObjectiveAppendiceal diameter is a primary sonographic determinant of paediatric appendicitis. We sought to determine if the diagnostic performance of outer appendiceal diameter differs based on age or with the addition of secondary sonographic findings.MethodsWe retrospectively reviewed patients aged less than 19 years who presented to the Boston Children’s Hospital ED and had an ultrasound (US) for the evaluation of appendicitis between November 2015 and October 2018. Our primary outcome was the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Our results agree with previous studies that reported that the appendiceal caliber was a strong predictor of PAA [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with previous studies that reported that the appendiceal caliber was a strong predictor of PAA [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…In relation to radiological studies for the diagnosis of PAA, abdominal ultrasound (AUS) has an excellent diagnostic yield [ 6 ], especially when combined with clinical and analytical scores (such as PAS score or Alvarado score) [ 1 ]. However, AUS is an operator-dependent test and visualization of the appendix is not achieved in all patients, so it cannot be considered a definitive diagnostic test [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to radiological studies for the diagnosis of PAA, abdominal ultrasound (AUS) has an excellent diagnostic yield [ 6 ], especially when combined with clinical and analytical scores (such as PAS score or Alvarado score) [ 1 ]. However, AUS is an operator-dependent test and visualization of the appendix is not achieved in all patients, so it cannot be considered a definitive diagnostic test [ 6 , 7 ]. It should be noted that the use of computed tomography (CT) in the setting of PAA is limited due to the significant radiation dose associated with this particularly vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Across all age groups, the optimal appendiceal diameter threshold is 7 mm for the diagnosis of paediatric appendicitis. 27 Inclusion criteria included all the following: (1) Imaging-confirmed uncomplicated appendicitis by ultrasound or CT: increase in the calibre of the appendix, measured at more than 6 mm in diameter with non-compressibility, localised free fluid, increased echogenicity of periappendiceal fat; (2) Age 5–15 years; (3) Non-septic clinical aspect (good general condition, normal haemodynamic status, normal diuresis); (4) Intravenous and oral antibiotic regimen by amoxicillin-clavulanic acid; (5) Parental good understanding of the monitoring instructions. Exclusion criteria included any of the following: (1) Ultrasound or CT scan showing one or several stercoliths, an abscess, appendicular mass or generalised peritonitis; (2) Primary or secondary immune deficiency; (3) Parental refusal of research protocol; (4) Impossibility of home follow-up after discharge from hospital; (5) Allergy to penicillin.…”
Section: Methodsmentioning
confidence: 99%